2011
DOI: 10.1097/iop.0b013e3181eea7d7
|View full text |Cite
|
Sign up to set email alerts
|

Patient Experience With Blepharoplasty

Abstract: Postoperative patient experience with blepharoplasty is based largely on anecdotal evidence; the data from this study will facilitate more objectively based preoperative counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Upper blepharoplasty is the goldstandard procedure for correction of dermatochalasis. 5 Blepharoplasty improves abnormal eyelid cosmesis and functionality by removing excess skin and, if required, muscle or fat. It has been reported that blepharoplasty results in improvement in patients' visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Upper blepharoplasty is the goldstandard procedure for correction of dermatochalasis. 5 Blepharoplasty improves abnormal eyelid cosmesis and functionality by removing excess skin and, if required, muscle or fat. It has been reported that blepharoplasty results in improvement in patients' visual function.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects were asked to rate each parameter on a scale of 0 to 10, with 0 representing absent and 10 representing the most severe level that the patient could imagine. 8,9 Before the questionnaire was administered, the patients were told that they were required to anticipate the degree of postoperative pain, daily life disruption, and PONV lasting for less than 3 days, and blurred vision, diplopia, foreign body sensation, conjunctival redness, and eyelid swelling lasting from 1 to 4 weeks. Patient expectations were evaluated, using the questionnaire, both before and after strabismus surgery.…”
Section: Methodsmentioning
confidence: 99%
“…4 Prior studies have addressed patient satisfaction following blepharoplasty, but there is a dearth of literature specifically analyzing the primary pre-and postoperative queries and concerns of patients. [5][6][7][8] As with many elective cosmetic procedures, patients present with a list of questions that frequently influence their decision to pursue surgical intervention. In fact, an analysis of plastic surgery satisfaction by Chen et al found that one of the highest correlated factors for a patient to recommend a practice or provider to someone else was the provider's ability to address patient questions.…”
Section: Introductionmentioning
confidence: 99%